Penyusunan Indeks Beranotasi Artikel tentang Minangkabau dalam Surat Kabar Padang Ekspres Tahun 2017 - Putri, Rini Amanda; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ This working paper discusses about to manage index of annotation about Minangkabausm in Padang Ekspres newspaper 2017. The method is used in this working paper is descriptive research of method is to collect the datum of real sources fluently of Padang Ekspres newspaper. Thehe are some ways in managing of indexs annotation of articles about Minangkabausim consists of ninth ways as: 1) to do observation for the news paper is, 2) to select the newspaper articles, 3) to make clipping of newspaper, 4) to make description of newspaper articles, 5) to make annotation, 6) to determine the key words, 7) to make index of newspaper articles, 8) to manage index annotation base on subject, 9) to type index annotation, the key words in index, the outhor index. The second, obstacles and efforts are faced in doing to manage annotation index as: 1) to abstacle to doing solution newspaper can be overcome by classify the date of letter based on the publisher time, 2) the newspaper are not complete available can be overcome by making the list of information abot the newspaper completeness, 3) to storage the newspaper are just put in store room, as well as can put in the collection shelfs.Keyword: index of annotation, Padang Ekspres newspaper, Minangkabau